2015
DOI: 10.1177/1069072714565780
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Scientific Communication Self-efficacy, Interest, and Outcome Expectations for Career Development in Academic Medicine

Abstract: Competency in forms of scientific communication, both written and spoken, is essential for success in academic science. This study examined the psychometric properties of three new measures, based on social cognitive career theory, that are relevant to assessment of skill and perseverance in scientific communication. Pre- and postdoctoral trainees in biomedical science (N = 411) completed online questionnaires assessing self-efficacy in scientific communication, career outcome expectations, and interest in per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…), and science identity. An earlier cross-sectional study found that at the PhD and postdoctoral level engagement in SC and social cognitive variables were predictive of intention to pursue an academic research career [13]. The longitudinal study reported here builds on this work by testing temporal relations between these variables, with the addition of science identity.…”
Section: Language Identity and Scientific Communicationmentioning
confidence: 78%
See 4 more Smart Citations
“…), and science identity. An earlier cross-sectional study found that at the PhD and postdoctoral level engagement in SC and social cognitive variables were predictive of intention to pursue an academic research career [13]. The longitudinal study reported here builds on this work by testing temporal relations between these variables, with the addition of science identity.…”
Section: Language Identity and Scientific Communicationmentioning
confidence: 78%
“…SC productivity. At Time 1, trainees were asked to write in the number of SC tasks they had completed in their career to date [13,39]. These included two types of writing tasks (e.g., "Prepared by myself a full first draft of a first-author manuscript [does not have to have been submitted]") and two presentation-task items (e.g., "Given an oral presentation at a national scientific meeting" and "How many times have you presented a poster at a scientific meeting?").…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations